Analytical Laboratory at Dearborn Chemical Company facility - Dearborn Chemical Company (1962)
General view of employees at work in the Analytical Laboratory at the Dearborn Chemical Company's 35th Street laboratory facility located in Chicago, Illinois. The two employees visible in the foreground of the photograph are identified as Valentine I. Miciulis and Hazel Mueller. Founded in 1887, the Dearborn Chemical Company was a corporate ancestor of BetzDearborn, Incorporated best known for manufacturing water treatment chemicals for use in boilers and cooling towers.
Keywords: Women in science; Employees; Chemical industry; Laboratories; Water purification chemicals industry; Corporations; Women employees; Glassware; Dearborn Chemical Company